THE INTELLECTUAL, SOCIAL, AFFECTIVE ENGAGEMENT SCALE (ISA ENGAGEMENT SCALE): A VALIDATION STUDY - Sidharta, Iwan (JURNAL COMPUTECH & BISNIS, 2019)
The critical role of employee management in organizational development is one of the goals of the organization. This study aims to validate the Intellectual, Social, Affective Engagement Scale (ISA Engagement Scale) instrument developed by Soane et al. (2012) using local samples and the manufacturing and service sectors. Participants in this study were 112 employees who filled out the questionnaire. Determination of a random sample by giving an instrument statement to respondents who are willing to fill in instruments that have been provided by researchers. The data testing method uses exploratory factor analysis (EFA) by first testing the validity and reliability of the instrument. The results showed that it proves that the ISA instrument had three unique factors, namely the cumulative variance extracted rate of 65%. The result indicates that the ISA instrument can be used to measure employee engagement. Keywords : Employee Engagement, Validation, Exploratory Factor Analysis.